Pengaruh Religiusitas, Perawatan Diri, dan Mekanisme Koping Pada Kualitas Hidup Pasien Diabetes Mellitus - Rosliana Dewi; Santhna Letchmi Panduragan; Nur Syazana Umar; Fera Melinda; Johan Budhiana (Faculty of Nursing Universitas Padjadjaran, 2022)
Background: Uncontrolled diabetes is at a high risk for complications. This chronic complication can cause a decrease in the quality of life of DM patients. There are several factors that affect the quality of life of people with diabetes. Religiosity, self-care, and coping mechanisms together affect the quality of life. Religiosity is very important for patients to have as a foundation for maintaining quality of life. Self-care is a basic effort to control and prevent complications arising from DM. Coping mechanisms are problem-solving efforts and defense mechanisms used to protect themselves from DM problems. Purpose: This study aims to determine the effect of religiosity, self-care, and coping mechanisms on the quality of life of DM sufferers. Methods: This study uses a quantitative research design and a cross-sectional approach involving 130 respondents, using a total sampling technique. Data was collected using various questionnaires, including a Centrality Religiosity Scale (CRS) questionnaire, Summary of Diabetes Self-Care Activity (SDSCA), Coping Orientation to Problem Experienced (COPE), and Diabetes Quality of Life (DQOL). Inclusion criteria were patients with type 2 diabetes mellitus with blood glucose levels  200 mg/dl and patients with type 2 diabetes who had diabetes > 1 year or more. Path Analysis is used to analyze data. Results: The religiosity of patients with type 2 diabetes has a mean of 49.47, a mean of 42.59 for self-care, a mean of 85.29 for coping mechanisms, and a mean of 42.56 for quality of life. There is an effect of religiosity (p = 0.000), coping mechanisms (p = 0.001), and self-care (p = 0.000) on the quality of life. Conclusion: Religiosity, coping mechanisms, and self-care affect the quality of life of people with Type 2 DM. Efforts that can be made by the hospital to increase health promotion related to improving the quality of life of people with diabetes mellitus.